A solution-processed bis-tridentate iridium(iii) complex-cored dendrimer for green OLEDs. Issue 30 (8th July 2021) - Pandit, Vaidehi; Jang, Junhyuk; Babazadeh, Mohammad; Ranasinghe, Chandana Sampath Kumara; Huang, David M.; Burn, Paul L.; Puttock, Emma V.
Abstract : We report a solution-processable dendronised bis-tridentate iridium(iii ) complex composed of a bis(imidazolyl)phenyl ligand with a first-generation biphenyl dendron containing t -butyl surface groups and a 2-pyrazolyl-6-phenylpyridine co-ligand. Abstract : We report the first example of a solution-processable dendronised bis-tridentate iridium(iii ) complex composed of a bis(imidazolyl)phenyl ligand with a first-generation biphenyl dendron containing t -butyl surface groups and a 2-pyrazolyl-6-phenylpyridine co-ligand. The non-dendronised analogue and the dendrimer were found to emit green light. Both complexes were found to have a solution photoluminescence quantum yield [PLQY ( Φ )] of ∼70% in toluene. The PLQY of both complexes was reduced in the neat film due to intermolecular quenching. However, the dendrimer retained a higher portion of its PLQY ( Φ = 22% versus 9%) in the neat film due to the dendrons partially shielding the emissive iridium(iii ) complex at its core. The solid-state intermolecular interchromophore interactions of the dendronised complex were suppressed by blending with tris(4-carbazoyl-9-ylphenyl)amine (TCTA) and the PLQY increased to 65%. The non-dendronised material had insufficient solubility to enable it to be solution processed to form films of sufficient thickness and quality to be used as the emissive material in an organic light-emitting diode (OLED). In contrast, the dendronised complex was amenable to solution coating techniques and simple two-layer OLEDs comprising a neat dendrimer film or films with 10 wt% of the dendrimer in TCTA and an electron transport layer showed green emission with maximum external quantum efficiency of 4.5% and 10.7%, respectively.